Quitter : closing the gap between your day job & your dream job - Acuff, Jonathan M. (Lampo Press, The Lampo Group, 2011)
Many people think that dreaming big means you quit your day job, and sell everything you own. What if there were a different way. This book is based on Acuff's experience in cultivating a dream job that changed his life-- and the world in the process.